2015
DOI: 10.1136/jmedgenet-2015-103366
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent copy number variations as risk factors for neurodevelopmental disorders: critical overview and analysis of clinical implications

Abstract: Neurodevelopmental disorders (NDs) encompass a spectrum of neuropsychiatric manifestations. Chromosomal regions 1q21.1, 3q29, 15q11.2, 15q13.3, 16p11.2, 16p13.1 and 22q11 harbour rare but recurrent CNVs that have been uncovered as being important risk factors for several of these disorders. These rearrangements may underlie a broad phenotypical spectrum, ranging from normal development, to learning problems, intellectual disability (ID), epilepsy and psychiatric diseases, such as autism spectrum disorders (ASD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 162 publications
3
76
0
Order By: Relevance
“…Analyzing the 4 selected studies on short stature as well as the present study, 7 recurrent CNVs and 1 uniparental disomy were identified in patients with short stature of unknown cause. These CNVs were characterized as large, de novo, and individually rare, similar to those from other conditions in which there might be genetic “hotspots” for chromosomal imbalances [19, 20]. These loci corresponded to 40.2% of the total pathogenic or probably pathogenic CNVs described in all studies in which the short stature phenotype was the main emphasized phenotype.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Analyzing the 4 selected studies on short stature as well as the present study, 7 recurrent CNVs and 1 uniparental disomy were identified in patients with short stature of unknown cause. These CNVs were characterized as large, de novo, and individually rare, similar to those from other conditions in which there might be genetic “hotspots” for chromosomal imbalances [19, 20]. These loci corresponded to 40.2% of the total pathogenic or probably pathogenic CNVs described in all studies in which the short stature phenotype was the main emphasized phenotype.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, studies have recognized recurrent pathogenic or probably pathogenic CNVs associated with neurodevelopment disorders, ovarian cancer, and heart diseases, indicating that there might be some genetic “hotspots” predisposing to different diseases [19-21]. Analyzing the 4 selected studies on short stature as well as the present study, 7 recurrent CNVs and 1 uniparental disomy were identified in patients with short stature of unknown cause.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we screened for the lincRNAs that showed expression changes due to copy number alterations ( p < 0.05 according to t ‐test). CNVs are considered as risk factors for cancer, as these large‐sized genomic alterations may encompass key genes that contribute to carcinogenesis and disease progression . These copy number altered lincRNAs were termed as risk lincRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…However, if significant in terms of either the number and/or functional significance of the genes involved, they can be associated with a clinical phenotype. Some of these CNVs are recurrent and are now being categorised as syndromes 3. However, as with most genetic conditions, there is often variable expression or reduced penetrance 4…”
Section: Advances In Testingmentioning
confidence: 99%